Comprehensive surgical intervention on the anterior and posterior parts of the eye for untimely diagnosed subconjunctival scleral rupture - Сідак-Петрецька, Оксана Степанівна; Ульянова, Надія Анатоліївна; Бондар, Наталія Ігорівна; Якименко, Ірина; Пономарчук, Олександр Валерійович (My University, 2025)
Purpose To determine the tactics of surgical treatment in the anterior and posterior segments of the eye in case of untimely sutured subconjunctival scleral rupture (SCSR). Setting/Venue Clinical retrospective study was perfomed in the Post-Traumatic Eye Pathology Department Methods The results of complex surgical treatment of 15 patients (15 eyes) with severe closed combat and civilian eye trauma accompanied by undiagnosed SCRS were analyzed. All patients were male, aged 26 to 77 years, an average age of 52 years. Before applying to our department, the patients were examined and treated in other clinics, and scleral inspection for rupture was not performed. Visual acuity (VA) ranged from light perception with incorrect light projection to 0.02. All eyes were hypotonic. The cataract, vitreous fibrosis, detachment of retina, ciliary body and choroid were diagnosed in all patients. Initial phtisis bulbi was set in 3 eyes. SCRS of various localization was detected during combined pars plana vitrectomy (VE) 23-25Ga with cataract extraction. After scleral wound suturing, all cases underwent retinotomy around the scleral rupture, retinal flattening using perfluorocarbon liquids, endolaser coagulation, and tamponade: air-gas mixture (C3F8) or silicone oil (5700 cSt). Some cases included iridoplasty and intraocular lens implantation. Results Outcomes were evaluated based on VA, intraocular pressure (IOP), ultrasound biometry and reattachment of layers. One year after surgery, all patients retained functional vision (0.02–0.3 with correction), with IOP within 14–22 mmHg. The retina and choroid remained attached in all cases. Low VA was due to the development of epimacular fibrosis and secondary cataract . Conclusions Thus, in cases of severe blunt trauma of the eyeball with suspected SCRS, a scleral revision in all segments of the eyeball, especially at the site of attachment of the rectus muscles, should be performed, and if there are indications for VE, it should be conducted as early as possible after the trauma, before the beginning of active proliferation.